Effects of adalimumab therapy in adult subjects with moderate‐to‐severe psoriasis on Th17 pathway. (4th September 2013) - Balato, A.; Schiattarella, M.; Di Caprio, R.; Lembo, S.; Mattii, M.; Balato, N.; Ayala, F.
Abstract Background Until relatively recently, psoriasis has been considered to be a mainly T helper (Th)1‐driven inflammatory disease; however, several findings have now assessed a major role for Th17 cells in its pathogenesis. Adalimumab is a biological agent that inhibits TNF‐α, a pro‐inflammatory cytokine with a pivotal role in the mechanisms of the disease. Objective To elucidate the in vivo effects of adalimumab therapy on Th17 pathway. Methods Quantitative real‐time reverse transcriptase polymerase chain reaction was used to analyse levels of expression of Th17 polarizing cytokines (IL‐23A, TGF‐β, IL‐1β, IL‐6), Th17 cytokines (IL‐17, IL‐22) as well as TNF‐α, Th1 polarizing cytokine (IFN‐α) and Th17 downstream effector mediators, such as chemokines (IL‐8, CCL‐20) in skin and peripheral blood mononuclear cells before and after 16 weeks of adalimumab therapy. Similarly, gene expression of Th17 induced mediators by keratinocytes (antimicrobial peptides: HBD‐2, S100A7) was investigated at skin level. In addition, cutaneous and plasma IL‐17 was examined by immunohistochemistry and enzyme‐linked immunosorbent assay respectively. Efficacy of the treatment was assessed by several clinical index scores as well as epidermal thickness reduction. Results Adalimumab therapy led to improvement in skin disease scores in all patients. Moreover, adalimumab treatment down‐modulated Th17 pathway at skin level. Plasma IL‐17 levels and IL‐17‐positive cells in psoriatic lesional skin were decreased by adalimumab treatment. Conclusions Our data highlight that the immunomodulatory activity of adalimumab is associated with considerable clinical improvements as well as a potent shut down of Th17 response in patients with moderate‐to‐severe psoriasis.